Denitration catalyst Ce-Sb-Mo / TiO2 with wide temperature window and high water resistance and preparation method of denitration catalyst Ce-Sb-Mo / TiO2
By using Ce-Sb-Mo/TiO2 catalyst, the problem of narrow temperature windows and insufficient water and sulfur resistance in the prior art is solved, and the effect of efficient conversion of NOx within a wide temperature range is achieved.
Patent Information
- Application Number
- CN202411860535.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
AI Technical Summary
In the existing nitrogen oxide selective catalytic reduction technology, the temperature window of the catalyst is narrow and its resistance to water and sulfur dioxide is insufficient, resulting in a reduced denitrification efficiency and a higher cost.
Ce-Sb-Mo/TiO2 is used as a denitrogenation catalyst with high water resistance performance in a wide temperature window. By treating cerium nitrate hexahydrate, antimony trichloride, ammonium hexamolybdate tetrahydrate and titanium dioxide powder in specific proportions and conditions, a uniformly supported catalyst is formed.
It achieves efficient conversion of NOx within the temperature range of 250-480℃, has good water and sulfur resistance, extends the service life of the catalyst, and improves denitrification efficiency.
Smart Images

Figure CN119680528A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst materials, and more specifically to a Ce-Sb-Mo / TiO2 denitration catalyst with a wide temperature window and high water resistance and a preparation method thereof. Background Art
[0002] With the development of society, environmental issues have attracted more and more attention, and the harm of nitrogen oxides to the environment has caused many problems, such as greenhouse effect, acid rain, photochemical smog, and ozone depletion. The selective catalytic reduction of nitrogen (NH3-SCR) can effectively solve this problem. The selective catalytic reduction technology of nitrogen is a widely used denitrification technology. The most widely used catalyst in commercial use is V2O5-WO3 / TiO2 catalyst, but the temperature window of this catalyst is narrow (300-400℃). During the reaction process, VO x It is a highly toxic oxide that can cause alkali metal poisoning of the catalyst at high temperatures, reduce the activity of the catalyst, and cause great harm to the environment. These disadvantages limit the application of V2O5-WO3 / TiO2 catalysts, especially the low-temperature activity will allow new process configurations in exhaust gas treatment to reduce catalyst deactivation caused by dust.
[0003] At present, there are many types of catalysts in selective catalytic reduction technology, which are harmful to the environment. The temperature window of the catalyst is narrow, and the expected denitrification efficiency cannot be achieved in a certain temperature range. Water and sulfur dioxide are often present in the flue gas duct, which will reduce the denitrification efficiency of the catalyst when the catalyst is used. The catalyst cost is high.
[0004] Therefore, how to develop a wide temperature window and high water resistance denitrification catalyst Ce-Sb-Mo / TiO2 and its preparation method for the later stage treatment of nitrogen oxides in exhaust flue gas to improve the efficiency of converting nitrogen oxides into nitrogen and water is an urgent problem to be solved by technicians in this field. Summary of the invention
[0005] In view of this, the present invention provides a Ce-Sb-Mo / TiO2 denitration catalyst with a wide temperature window and high water resistance and a preparation method thereof.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A method for preparing a Ce-Sb-Mo / TiO2 denitration catalyst with a wide temperature window and high water resistance, comprising the following steps:
[0008] (1) adding cerium nitrate hexahydrate, antimony trichloride and ammonium heptamolybdate tetrahydrate into deionized water, dissolving them by ultrasonication, and then stirring them, and then adding titanium dioxide powder, and magnetically stirring them at room temperature to obtain a solution;
[0009] (2) NH3·H2O is added dropwise to the obtained solution to adjust the pH value to 10, and stirring is continued. Then, the solid is separated from the liquid, and the solid is washed with deionized water until it is neutral, dried, and calcined to obtain the wide temperature window and high water resistance denitration catalyst Ce-Sb-Mo / TiO2.
[0010] Beneficial effects of the present invention: The present invention uses industrial-grade TiO2 as a carrier, cerium, antimony and molybdenum as active components, and ammonia water as a precipitant, and under long-term stirring, the active components cerium, antimony and molybdenum are uniformly loaded on the TiO2 carrier. Antimony and molybdenum are used to modify the Ce / TiO2 catalyst, which enhances the active sites of the Ce / TiO2 catalyst, prolongs the service life, and broadens the temperature window, water and sulfur resistance, surface acidity and redox ability of the Ce / TiO2 catalyst, so that the catalyst has a high conversion rate for NOx in the temperature range of 250-480°C, and can be widely used in industrial production.
[0011] Furthermore, in step (1), the addition ratio of cerium nitrate hexahydrate, antimony trichloride, ammonium heptamolybdate tetrahydrate, titanium dioxide powder and deionized water is: 1.2614 g cerium nitrate hexahydrate, 0.6627 g antimony trichloride, 0.3590-3.5902 g ammonium heptamolybdate tetrahydrate, and 5 g titanium dioxide powder per 100 mL deionized water.
[0012] Furthermore, in step (1), the titanium dioxide powder is anatase titanium dioxide powder with a particle size of 5-10 nm.
[0013] Furthermore, in step (1), cerium nitrate hexahydrate, antimony trichloride and ammonium heptamolybdate tetrahydrate are added to deionized water for ultrasonic dissolution, the ultrasonic power is 80W, the ultrasonic time is 10min, and then stirred, the stirring speed is 500rpm, and the stirring time is 20min.
[0014] Beneficial effects of adopting the above further technical solution: The effect of ultrasound is to dissolve the reagent in water better. After 10 minutes at a power of 80W, the reagent will be completely dissolved in water, and the effect will be better if stirring is added.
[0015] Furthermore, in step (1), titanium dioxide powder was added and magnetic stirring was performed at room temperature with a stirring speed of 500 rpm and a stirring time of 1 h.
[0016] The beneficial effect of adopting the above further technical solution is that the titanium dioxide is fully mixed with the solvent.
[0017] Furthermore, in step (2), stirring was continued for 4 h at a stirring speed of 500 rpm.
[0018] Furthermore, in step (2), the drying temperature is 80° C. and the drying time is 12 h.
[0019] Furthermore, in step (2), the calcination step is as follows: heating from room temperature to 500° C. at a heating rate of 5° C. / min and keeping the temperature for 4 hours.
[0020] The present invention also provides a Ce-Sb-Mo / TiO2 denitration catalyst with a wide temperature window and high water resistance prepared by the above method.
[0021] Beneficial effects of the present invention: The cerium-based catalyst of the present invention has a wide temperature window, strong water and sulfur resistance, strong redox ability and surface acidity, and a wide temperature window of the vanadium-tungsten catalyst of the present invention. It is used for the post-treatment of nitrogen oxides in tail gas and flue gas, and uses ammonia as a reducing agent to improve the efficiency of converting nitrogen oxides into nitrogen and water. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Comparative Example 1-3 Relationship between NO conversion rate and temperature of Ce-Sby / TiO2 catalyst;
[0023] Figure 2 Relationship between NO conversion rate and temperature of catalysts of Examples 1-6, Comparative Example 1, Comparative Example 4, and Comparative Example 5;
[0024] Figure 3 Relationship between NO conversion rate and temperature after adding water to the catalyst of Examples 1-6, Comparative Example 1, and Comparative Example 4;
[0025] Figure 4 Comparative Example 4 Ce / TiO2, Comparative Example 1 Ce-Sb / TiO2, Example 1 Ce-Co-Mo / TiO2 three catalytic water and sulfur resistance tests;
[0026] Figure 5 Oxygen reduction capacity of Comparative Example 4 Ce / TiO2, Comparative Example 1 Ce-Sb / TiO2, and Example 1 Ce-Co-Mo / TiO2;
[0027] Figure 6 Surface acidity of Ce / TiO2 in Comparative Example 4, Ce-Sb / TiO2 in Comparative Example 1, and Ce-Sb-Mo / TiO2 in Example 1. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] A method for preparing a Ce-Sb-Mo / TiO2 denitration catalyst with a wide temperature window and high water resistance comprises the following steps:
[0031] (1) 1.2614 g of cerium nitrate hexahydrate, 0.6627 g of antimony trichloride and 1.7951 g of ammonium heptamolybdate tetrahydrate were added to 100 mL of deionized water for ultrasonic dissolution, with an ultrasonic power of 80 W and an ultrasonic time of 10 min, followed by stirring at a stirring speed of 500 rpm for 20 min, and then 5 g of anatase titanium dioxide powder with a particle size of 5-10 nm was added, and magnetic stirring was performed at room temperature at a stirring speed of 500 rpm for 1 h to obtain a solution;
[0032] (2) NH3·H2O was added dropwise to the obtained solution to adjust the pH to 10, and the stirring was continued for 4 h at a stirring speed of 500 rpm. Then, the solid was separated from the liquid, and the solid was washed with deionized water until it was neutral, and dried at a drying temperature of 80°C for 12 h. The solid was calcined in a muffle furnace at a heating rate of 5°C / min from room temperature to 500°C and kept warm for 4 h to obtain Ce-Sb-Mo x / TiO2, x = the molar ratio of Mo / Ce, x = 0.5, recorded as Ce-Sb-Mo 0.5 / TiO2.
[0033] Example 2
[0034] A method for preparing a Ce-Sb-Mo / TiO2 denitration catalyst with a wide temperature window and high water resistance comprises the following steps:
[0035] (1) 1.2614 g of cerium nitrate hexahydrate, 0.6627 g of antimony trichloride and 0.3590 g of ammonium heptamolybdate tetrahydrate were added to 100 mL of deionized water for ultrasonic dissolution, with an ultrasonic power of 80 W and an ultrasonic time of 10 min, followed by stirring at a stirring speed of 500 rpm for 20 min, and then 5 g of anatase titanium dioxide powder with a particle size of 5-10 nm was added, and magnetic stirring was performed at room temperature at a stirring speed of 500 rpm for 1 h to obtain a solution;
[0036] (2) NH3·H2O was added dropwise to the obtained solution to adjust the pH to 10, and the stirring was continued for 4 h at a stirring speed of 500 rpm. Then, the solid was separated from the liquid, and the solid was washed with deionized water until it was neutral, and dried at a drying temperature of 80°C for 12 h. The solid was calcined in a muffle furnace at a heating rate of 5°C / min from room temperature to 500°C and kept warm for 4 h to obtain Ce-Sb-Mo x / TiO2, x = the molar ratio of Mo / Ce, x = 0.1, recorded as Ce-Sb-Mo 0.1 / TiO2.
[0037] Example 3
[0038] A method for preparing a Ce-Sb-Mo / TiO2 denitration catalyst with a wide temperature window and high water resistance comprises the following steps:
[0039] (1) 1.2614 g of cerium nitrate hexahydrate, 0.6627 g of antimony trichloride and 1.0771 g of ammonium heptamolybdate tetrahydrate were added to 100 mL of deionized water for ultrasonic dissolution, with an ultrasonic power of 80 W and an ultrasonic time of 10 min, followed by stirring at a stirring speed of 500 rpm for 20 min, and then 5 g of anatase titanium dioxide powder with a particle size of 5-10 nm was added, and magnetic stirring was performed at room temperature at a stirring speed of 500 rpm for 1 h to obtain a solution;
[0040] (2) NH3·H2O was added dropwise to the obtained solution to adjust the pH to 10, and the stirring was continued for 4 h at a stirring speed of 500 rpm. Then, the solid was separated from the liquid, and the solid was washed with deionized water until it was neutral, and dried at a drying temperature of 80°C for 12 h. The solid was calcined in a muffle furnace at a heating rate of 5°C / min from room temperature to 500°C and kept warm for 4 h to obtain Ce-Sb-Mo x / TiO2, x = the molar ratio of Mo / Ce, x = 0.3, recorded as Ce-Sb-Mo 0.3 / TiO2.
[0041] Example 4
[0042] A method for preparing a Ce-Sb-Mo / TiO2 denitration catalyst with a wide temperature window and high water resistance comprises the following steps:
[0043] (1) 1.2614 g of cerium nitrate hexahydrate, 0.6627 g of antimony trichloride and 2.5131 g of ammonium heptamolybdate tetrahydrate were added to 100 mL of deionized water for ultrasonic dissolution, with an ultrasonic power of 80 W and an ultrasonic time of 10 min, followed by stirring at a stirring speed of 500 rpm for 20 min, and then 5 g of anatase titanium dioxide powder with a particle size of 5-10 nm was added, and magnetic stirring was performed at room temperature at a stirring speed of 500 rpm for 1 h to obtain a solution;
[0044] (2) NH3·H2O was added dropwise to the obtained solution to adjust the pH to 10, and the stirring was continued for 4 h at a stirring speed of 500 rpm. Then, the solid was separated from the liquid, and the solid was washed with deionized water until it was neutral, and dried at a drying temperature of 80°C for 12 h. The solid was calcined in a muffle furnace at a heating rate of 5°C / min from room temperature to 500°C and kept warm for 4 h to obtain Ce-Sb-Mo x / TiO2, x = the molar ratio of Mo / Ce, x = 0.7, recorded as Ce-Sb-Mo 0.7 / TiO2.
[0045] Example 5
[0046] A method for preparing a Ce-Sb-Mo / TiO2 denitration catalyst with a wide temperature window and high water resistance comprises the following steps:
[0047] (1) 1.2614 g of cerium nitrate hexahydrate, 0.6627 g of antimony trichloride and 3.2312 g of ammonium heptamolybdate tetrahydrate were added to 100 mL of deionized water for ultrasonic dissolution, with an ultrasonic power of 80 W and an ultrasonic time of 10 min, followed by stirring at a stirring speed of 500 rpm for 20 min, and then 5 g of anatase titanium dioxide powder with a particle size of 5-10 nm was added, and magnetic stirring was performed at room temperature at a stirring speed of 500 rpm for 1 h to obtain a solution;
[0048] (2) NH3·H2O was added dropwise to the obtained solution to adjust the pH to 10, and the stirring was continued for 4 h at a stirring speed of 500 rpm. Then, the solid was separated from the liquid, and the solid was washed with deionized water until it was neutral, and dried at a drying temperature of 80°C for 12 h. The solid was calcined in a muffle furnace at a heating rate of 5°C / min from room temperature to 500°C and kept warm for 4 h to obtain Ce-Sb-Mo x / TiO2, x = the molar ratio of Mo / Ce, x = 0.9, recorded as Ce-Sb-Mo 0.9 / TiO2.
[0049] Example 6
[0050] A method for preparing a Ce-Sb-Mo / TiO2 denitration catalyst with a wide temperature window and high water resistance comprises the following steps:
[0051] (1) 1.2614 g of cerium nitrate hexahydrate, 0.6627 g of antimony trichloride and 3.5902 g of ammonium heptamolybdate tetrahydrate were added to 100 mL of deionized water for ultrasonic dissolution, with an ultrasonic power of 80 W and an ultrasonic time of 10 min, followed by stirring at a stirring speed of 500 rpm for 20 min, and then 5 g of anatase titanium dioxide powder with a particle size of 5-10 nm was added, and magnetic stirring was performed at room temperature at a stirring speed of 500 rpm for 1 h to obtain a solution;
[0052] (2) NH3·H2O was added dropwise to the obtained solution to adjust the pH to 10, and the stirring was continued for 4 h at a stirring speed of 500 rpm. Then, the solid was separated from the liquid, and the solid was washed with deionized water until it was neutral, and dried at a drying temperature of 80°C for 12 h. The solid was calcined in a muffle furnace at a heating rate of 5°C / min from room temperature to 500°C and kept warm for 4 h to obtain Ce-Sb-Mo x / TiO2, x=the molar ratio of Mo / Ce, x=1, recorded as Ce-Sb-Mo1 / TiO2.
[0053] Comparative Example 1
[0054] The preparation method of the denitration catalyst Ce-Sb / TiO2 comprises the following steps:
[0055] (1) 1.2614 g of cerium nitrate hexahydrate and 0.6627 g of antimony trichloride were added to 100 mL of deionized water for ultrasonic dissolution, with an ultrasonic power of 80 W and an ultrasonic time of 10 min, followed by stirring at a stirring speed of 500 rpm for 20 min, and then 5 g of anatase titanium dioxide powder with a particle size of 5-10 nm was added, and magnetic stirring was performed at room temperature at a stirring speed of 500 rpm for 1 h to obtain a solution;
[0056] (2) NH3·H2O was added dropwise to the obtained solution to adjust the pH to 10, and the stirring was continued for 4 h at a stirring speed of 500 rpm. Then, the solid was separated from the liquid, and the solid was washed with deionized water until it was neutral, and dried at a drying temperature of 80°C for 12 h. The solid was calcined in a muffle furnace at a heating rate of 5°C / min from room temperature to 500°C and kept warm for 4 h to obtain Ce-Sb y / TiO2, y=the molar ratio of Sb / Ce, y=1, recorded as Ce-Sb1 / TiO2.
[0057] Comparative Example 2
[0058] The preparation method of the denitration catalyst Ce-Sb / TiO2 comprises the following steps:
[0059] (1) 1.2614 g of cerium nitrate hexahydrate and 0.5302 g of antimony trichloride were added to 100 mL of deionized water for ultrasonic dissolution, with an ultrasonic power of 80 W and an ultrasonic time of 10 min, followed by stirring at a stirring speed of 500 rpm for 20 min, and then 5 g of anatase titanium dioxide powder with a particle size of 5-10 nm was added, and magnetic stirring was performed at room temperature at a stirring speed of 500 rpm for 1 h to obtain a solution;
[0060] (2) NH3·H2O was added dropwise to the obtained solution to adjust the pH to 10, and the stirring was continued for 4 h at a stirring speed of 500 rpm. Then, the solid was separated from the liquid, and the solid was washed with deionized water until it was neutral, and dried at a drying temperature of 80°C for 12 h. The solid was calcined in a muffle furnace at a heating rate of 5°C / min from room temperature to 500°C and kept warm for 4 h to obtain Ce-Sb y / TiO2, y = molar ratio of Sb / Ce, y = 0.8, recorded as Ce-Sb 0.8 / TiO2.
[0061] Comparative Example 3
[0062] The preparation method of the denitration catalyst Ce-Sb / TiO2 comprises the following steps:
[0063] (1) 1.2614 g of cerium nitrate hexahydrate and 0.7952 g of antimony trichloride were added to 100 mL of deionized water for ultrasonic dissolution, with an ultrasonic power of 80 W and an ultrasonic time of 10 min, followed by stirring at a stirring speed of 500 rpm for 20 min, and then 5 g of anatase titanium dioxide powder with a particle size of 5-10 nm was added, and magnetic stirring was performed at room temperature at a stirring speed of 500 rpm for 1 h to obtain a solution;
[0064] (2) NH3·H2O was added dropwise to the obtained solution to adjust the pH to 10, and the stirring was continued for 4 h at a stirring speed of 500 rpm. Then, the solid was separated from the liquid, and the solid was washed with deionized water until it was neutral, dried at a drying temperature of 80°C for 12 h, and calcined in a muffle furnace at a heating rate of 5°C / min from room temperature to 500°C, and kept at this temperature for 4 h to obtain a molar ratio of Ce-Sby / TiO2, y=Sb / Ce, y=1.2, recorded as Ce-Sb 1.2 / TiO2.
[0065] Comparative Example 4
[0066] The preparation method of denitration catalyst Ce / TiO2 comprises the following steps:
[0067] (1) 1.2614 g of cerium nitrate hexahydrate was added to 100 mL of deionized water and ultrasonically dissolved at an ultrasonic power of 80 W for 10 min, followed by stirring at a stirring speed of 500 rpm for 20 min, and then 5 g of anatase titanium dioxide powder with a particle size of 5-10 nm was added, and magnetic stirring was performed at room temperature at a stirring speed of 500 rpm for 1 h to obtain a solution;
[0068] (2) NH3·H2O was added dropwise to the obtained solution to adjust the pH value to 10, and stirring was continued for 4 hours at a stirring speed of 500 rpm. Then, the solid was separated from the liquid, and the solid was washed with deionized water until it was neutral. The solid was dried at a drying temperature of 80°C for 12 hours, and calcined in a muffle furnace at a heating rate of 5°C / min from room temperature to 500°C, and kept at this temperature for 4 hours to obtain Ce / TiO2.
[0069] Comparative Example 5
[0070] Denitration catalyst Ce-Mo 0.5 / The preparation method of TiO2 comprises the following steps:
[0071] (1) 1.2614 g of cerium nitrate hexahydrate and 1.7951 g of ammonium heptamolybdate tetrahydrate were added to 100 mL of deionized water for ultrasonic dissolution, with an ultrasonic power of 80 W and an ultrasonic time of 10 min, followed by stirring at a stirring speed of 500 rpm for 20 min, and then 5 g of anatase titanium dioxide powder with a particle size of 5-10 nm was added, and magnetic stirring was performed at room temperature at a stirring speed of 500 rpm for 1 h to obtain a solution;
[0072] (2) NH3·H2O was added dropwise to the obtained solution to adjust the pH to 10, and the stirring was continued for 4 h at a stirring speed of 500 rpm. Then, the solid was separated from the liquid, and the solid was washed with deionized water until it was neutral, and dried at a drying temperature of 80°C for 12 h. The solid was calcined in a muffle furnace at a heating rate of 5°C / min from room temperature to 500°C and kept warm for 4 h to obtain Ce-Mo x / TiO2, x = the molar ratio of Mo / Ce, x = 0.5, recorded as Ce-Mo 0.5 / TiO2.
[0073] The products of the examples and comparative examples were ground into 40-60 mesh particles for testing.
[0074] Figure 1 Comparative Examples 1-3 investigated the effects of different ratios of Ce-Sb1 / TiO2 catalysts on NO conversion, and the optimal catalysts were selected as Ce-Sb1 / TiO2, T 80 =230-450℃.
[0075] Figure 2 Effects of Examples 1-6, Comparative Examples 1, 4 and 5 on NO conversion, the optimal catalyst is Ce-Sb-Mo 0.5 / TiO2, T 80 =220-465℃.
[0076] Figure 3 When the catalysts of Examples 1-6, Comparative Examples 1 and 4 were added with H2O to test the effect on NO conversion, the best catalyst was Ce-Sb-Mo 0.5 / TiO2, T 80 =250-480+℃.
[0077] Figure 4 The water and sulfur resistance of Ce / TiO2 in comparative example 4, Ce-Sb / TiO2 in comparative example 1, and Ce-Co-Mo / TiO2 in example 1 are shown. The results show that the activity of Ce / TiO2 drops below 30%, the activity of Ce-Sb / TiO2 drops to 50%, and the lowest point of the drop of Ce-Co-Mo / TiO2 in example 1 is above 60%. After shutting off the water and sulfur, the activity of the Ce-Co-Mo / TiO2 catalyst in example 1 can be restored to 90%.
[0078] Figure 5 The redox ability of the catalysts of comparative example 4 Ce / TiO2, comparative example 1 Ce-Sb / TiO2, and example 1 Ce-Co-Mo / TiO2 was investigated. The results showed that the redox ability of example 1 Ce-Co-Mo / TiO2 was higher than that of the other two catalysts.
[0079] Figure 6 The surface acidity capabilities of comparative example 4 Ce / TiO2, comparative example 1 Ce-Sb / TiO2, and example 1 Ce-Co-Mo / TiO2 catalysts were investigated. The results showed that the surface acidity of example 1 Ce-Co-Mo / TiO2 was higher than that of the other two catalysts.
[0080] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a Ce-Sb-Mo / TiO2 denitration catalyst with a wide temperature window and high water resistance, characterized in that: The steps include: (1) adding cerium nitrate hexahydrate, antimony trichloride and ammonium heptamolybdate tetrahydrate into deionized water, dissolving them by ultrasonication, and then stirring them, and then adding titanium dioxide powder, and magnetically stirring them at room temperature to obtain a solution; (2) NH3·H2O is added dropwise to the obtained solution to adjust the pH value to 10, and stirring is continued. Then, the solid is separated from the liquid, and the solid is washed with deionized water until it is neutral, dried, and calcined to obtain the wide temperature window and high water resistance denitration catalyst Ce-Sb-Mo / TiO2.
2. The method for preparing a Ce-Sb-Mo / TiO2 denitration catalyst with a wide temperature window and high water resistance according to claim 1, characterized in that: In step (1), the addition ratio of cerium nitrate hexahydrate, antimony trichloride, ammonium heptamolybdate tetrahydrate, titanium dioxide powder and deionized water is: 1.2614g cerium nitrate hexahydrate, 0.6627g antimony trichloride, 0.3590-3.5902g ammonium heptamolybdate tetrahydrate, and 5g titanium dioxide powder per 100mL deionized water.
3. The method for preparing a Ce-Sb-Mo / TiO2 denitration catalyst with a wide temperature window and high water resistance according to claim 1, characterized in that: In step (1), the titanium dioxide powder is anatase titanium dioxide powder with a particle size of 5-10 nm.
4. The method for preparing a Ce-Sb-Mo / TiO2 denitration catalyst with a wide temperature window and high water resistance according to claim 1, characterized in that: In step (1), cerium nitrate hexahydrate, antimony trichloride and ammonium heptamolybdate tetrahydrate are added to deionized water for ultrasonic dissolution, the ultrasonic power is 80W, the ultrasonic time is 10min, and then stirred, the stirring speed is 500rpm, and the stirring time is 20min.
5. The method for preparing a Ce-Sb-Mo / TiO2 denitration catalyst with a wide temperature window and high water resistance according to claim 1, characterized in that: In step (1), titanium dioxide powder was added and magnetic stirring was performed at room temperature with a stirring speed of 500 rpm and a stirring time of 1 h.
6. The method for preparing a Ce-Sb-Mo / TiO2 denitration catalyst with a wide temperature window and high water resistance according to claim 1, characterized in that: In step (2), stirring was continued for 4 h at a stirring speed of 500 rpm.
7. The method for preparing a Ce-Sb-Mo / TiO2 denitration catalyst with a wide temperature window and high water resistance according to claim 1, characterized in that: In step (2), the drying temperature is 80° C. and the drying time is 12 h.
8. The method for preparing a Ce-Sb-Mo / TiO2 denitration catalyst with a wide temperature window and high water resistance according to claim 1, characterized in that: In step (2), the calcination step is: heating from room temperature to 500° C. at a heating rate of 5° C. / min and keeping the temperature for 4 hours.
9. A Ce-Sb-Mo / TiO2 denitration catalyst with a wide temperature window and high water resistance prepared by the method according to any one of claims 1 to 8.
Citation Information
Cited By
Preparation method of lanthanum-cerium co-doped composite titanium dioxide for automobile exhaust degradation
CN121534696A